Beş yaş çocukları için görsel algı, motor koordinasyon ve görsel-motor bütünleştirme testlerinin uyarlanması ve ilgili bir destek programının sınanması - Dibek, Esin (My University, 2010)
BEŞ YAŞ ÇOCUKLARI İÇİN GÖRSEL ALGI, MOTOR KOORDİNASYON VE GÖRSEL-MOTOR BÜTÜNLEŞTİRME TESTLERİNİN UYARLANMASI VE İLGİLİ BİR DESTEK PROGRAMININ SINANMASI Bu çalışma iki aşamadan oluşmaktadır. Çalışmanın birinci aşamasında Beery-5 Görsel Algı, Motor Koordinasyon ve Görsel-Motor Bütünleştirme Testlerinin (The Beery VMI Developmental Test of Visual-Motor Integration, Visual Peception, Motor Coordination, 2004) 5 yaş çocukları için uyarlanması amaçlanmıştır. İkinci aşamada, görsel algı, motor koordinasyon ve görsel-motor bütünleştirme becerilerini desteklemek üzere hazırlanan “Görsel-Motor Beceri Destek nın, çocukların hedeflenen becerilerdeki gelişimlerine olan etkisinin sınanması amaçlanmıştır. Araştırmanın geçerlik ve güvenirlik boyutunda çalışmalar, İstanbul İlindeki okul öncesi kurumlara devam eden 5 yaşındaki (60-71 ay) 258 çocukla gerçekleştirilmiştir. Geçerlik güvenirlik analizleri sonucunda testlerinin geçerlik ve güvenilirlik düzeylerinin yeterli olduğu görülmüştür. Araştırmada kullanılmak üzere araştırmacı tarafından görsel algı, motor koordinasyon ve görsel-motor bütünleştirme becerilerini geliştirmeye yönelik olarak Görsel-Motor Beceri Destek GMBDP) hazırlanmıştır. Program 10 ayrı resimli hikaye kitabından ve 2-3 boyutlu materyallerle desteklenen etkinliklerden oluşmaktadır. Araştırmaya yaşları 60-71 ay aralığında değişen, 17’si deney 16’sı kontrol toplam 33 çocuk alınmıştır. Deney ve kontrol gruplarının yaş ortalamaları 63 aydır. Program öncesinde GA, MK ve GMB testleri uygulanarak deney ve kontrol gruplarındaki çocukların eşitlenmiştir. Deney grubuna 10 hafta boyunca haftada 3 gün GMBDP uygulanmıştır. Kontrol grubundaki çocuklar ise normal eğitimlerine devam etmişlerdir. 10 haftalık program uygulaması sonrasında deney ve kontrol grubundaki çocuklara GA, MK ve GMB testleri tekrar uygulanmıştır. Deney ve kontrol gruplarının son testleri arasında MK ve GMB testlerinde .001, GA testinde .01 düzeyinde, deney grubundaki çocuklar lehine anlamlı farklılık bulunmuştur. Deney grubunun ön ve son testleri arasında tüm testlerde .001 düzeyinde anlamlı bir farklılık olduğu görülmüştür. Kontrol grubunun ön-son test değerlendirmelerinde MK ve GMB testlerinde anlamlı bir fark bulunmazken GA testinde .05 düzeyinde anlamlı farklılık görülmüştür. Bu sonuçlar uygulanan programın (GMEP) çocuklarda hedeflenen becerilerin gelişimini sağladığını göstermektedir. rsel algı, motor koordinasyon, görsel-motor bütünleştirme, okul öncesi eğitim

THE ADAPTATION STUDIES of VISUAL PERCEPTION MOTOR COORDINATION and VISUAL-MOTOR INTEGRATION TESTS for 5 YEARS-OLD CHILDREN into TURKISH and IMPLEMENTATION of VISUAL-MOTOR ABILITY ENHANCEMENT PROGRAM This study was conducted in two phases. In the first phase, it was aimed to realize adaptation of The Beery VMI Developmental Tests of Visual-Motor Integration, Visual Perception, Motor Coordination (2004) into Turkish for 5 years-old children. In the second phase, an empirical study on implementation of the “Visual-Motor Ability Enhancement Program” that was developed to support children’s visual perception, motor coordination, and visual-motor integration, was conducted. The subjects were 258 children aged between 60-71 months from pre-schools in the validity and reliability studies of the tests. The results indicated that the tests had statistically significant reliable and validity values. In this study, a “Visual-Motor Ability Enhancement Program” (VMAEP), including 10 separate pictorial story books and two or three dimensional education materials were developed by the researcher. For the second phase of the study, 33 children aged between 60-71 months were attained to experimental (17 children) and control (16 children) groups. The mean age of the children was 63 months. Before the implementation of the program, the tests of Visual Perception (VP), Motor Coordination (MK) and Visual-Motor Integration (VMI) were presented to the children from experimental and control groups and they were matched in terms of these tests results. The children in experimental group were implemented VMAEP for 10 weeks, 3 days in a week, but the children in control group attended the regular program in their classes. At the end of the 10 weeks education period of the program, the tests of VP, MK, and VMI were given to the children in both control and experimental groups again. The results revealed significant differences between VP (p<.01), MK and VMI (p<.001) post-test scores of the children in control and experimental groups. The children in experimental group got higher scores than the children in control group. In addition, the related analyses showed that the differences between pre and post-tests scores of the children in experimental group were statistically significant (p<.001). The differences between pre and post-test scores of the children on MK and VMI tests in control group were not significant, but the differences between pre and post-tests scores of the children on VP were statistically significant (p<.05). All these results indicated that VMAEP is an effective program for the development of children’s visual perception, motor- coordination and visual-motor integration skills. Key Words: Visual perception, motor-coordination, visual-motor integration, pre-school education.
Keywords: Eğitim_Okul Öncesi; Motor Öğrenme; Öğrenim ve Öğretim